Brain Abscess: A Rare Clinical Case with Oral Etiology - André João da Silva Pais Rocha Pereira; Ana Teresa Tavares; Marcelo Prates; Natacha Ribeiro; Luís Filipe Fonseca; Maria do Rosário Marques; Francisco Proença (Case Reports in Infectious Diseases)
Brain abscess is a very rare condition but has a significant mortality rate. The three main routes of inoculation are trauma, contiguous focus, and the hematogenous route. The odontogenic focus is infrequent and is usually a diagnosis of exclusion. This paper presents a brain abscess case proven to be of dental origin, caused by Actinomyces meyeri and Fusobacterium nucleatum. This case highlights the risk underlying untreated dental disease and why oral infectious foci removal and good oral health are essential in primary care.